"Mosaicking": cross construction, sense-making and methods of police investigation. Issue 4 (6th April 2021) - Innes, Martin; Brookman, Fiona; Jones, Helen
Abstract : Purpose: This article explores how homicide detectives make sense of and manipulate multiple physical, digital and informational artefacts when assembling case narratives. The authors introduce the concept of mosaicking to illuminate how different modes of information, deriving from different investigative methods, are used in concert at key moments of the investigative process – defining what type of crime has occurred; the incrimination and elimination of suspects; and decisions to charge key suspects. Design/methodology/approach: The data qualitatively analysed include several hundred case papers, interview transcripts ( n  = 144) and detailed ethnographic fieldnotes relating to 44 homicide investigations across four police services. These were collected during a four-year ethnographic study of the use of forensic sciences and technologies (FSTs) in British homicide investigations. Findings: Mosaicking describes how investigators blend and combine information, intelligence and evidence generated via different techniques and methods, to make sense of "who did what to whom and why?" Through processes of convergent and divergent mosaicking, detectives are able to "lean" on different kinds of material to reinforce or connect key points of evidence or intelligence. Originality/value: The findings fill a gap in knowledge about how investigators blend and composite diverse sources of information in the construction of case narratives. The findings present a more complex and nuanced understanding of the epistemological and interpretative work conducted by contemporary detectives, given the array of investigative technologies they increasingly have at their disposal.